Parent-child dynamics of cultural tensions between traditional and consumerist values through an identity perspective - Ruwangi Chandrasekara; Dinuka Wijetunga; J. A. S. K. Jayakody (Discover Psychology)
Abstract This study addresses a gap in literature by exploring how dynamic cultural forces between parents and children lead to paradoxical identity conflicts and related tensions. The study explores two distinct consumer categories. The results reveal that traditionally rooted parents consider dependent children as extensions of their identity and experience intense tensions due to the conflict between consumerist aspirations and traditional obligations toward children. They experience tensions due to discrepancies between an ideal self-guide or ought self-guide (both representing traditional values), an ideal self-guide (representing consumerist values at a level considered ideal) and a feared self (embracing too many consumerist values beyond what is considered ideal). The child, in turn, feels obliged to comply with parents’ traditional expectations despite their consumerist identity. They feel similar tensions just as their parents do, between conflicting value systems. In contrast, non-traditional parents do not use children as identity extensions; hence, they find no need to transfer personally rooted values to children and do not experience tensions. The findings contribute to literature on how children as contemporary consumers have implications with regard to identity and tensions of parents and vice versa. Accordingly, practitioners should cater products differently to target groups, based on specific value internalizations—the traditionally rooted parent and child are influenced by each other’s values during the buying decision process. However, marketers have the liberty of considering non-traditional parents and children as separate consumer categories as there are no interplay of values during the buying decision process. By such considerations marketers can successfully exploit consumer expectations and desires that would help address prevailing anxieties and cultural contradictions in society.